Open sesame. (Economist, 2008)
The article examines so-called "open-source hardware," electronic devices for which specifications have been made public. This allows enthusiasts to modify or build the devices, or write their own software for them. The process allows corporations to generate devices which satisfy consumers by incorporating market research and the prototype process.